UJI KESTABILAN SENYAWA TABIR SURYA - Riza Ummul Khusniah, ; Nurul Hidajati, (Matematika dan Sains, 2010)
The aim of research was to test the stability of the sunscreen 2-ethyl hexyl p-methoxycinnamate (EHPMS) in bentonite pillared Ti4+. The stability was determined by comparing with the sunscreen 2-ethyl hexyl p-methoxycinnamate without bentonite terpilar Ti4+ using TLC and IR spectrophotometer. The results of stability test showed that the EHPMS more stable in bentonite pillared Ti4+ matrix.4+. The stability was determined by comparing with the sunscreen 2-ethyl hexyl p-methoxycinnamate without bentonite terpilar Ti4+ using TLC and IR spectrophotometer. The results of stability test showed that the EHPMS more stable in bentonite pillared Ti4+ matrix.